فن الترمیق في تصمیم و تنفیذ فساتین السھرة و ملحقاتھا - بشرى فاضل صالح (College of Education for Women, 2019)
Abstract: If we neglect the value of historical fashions as a source of inspiration for contemporary fashion designers we will neglect a treasure of original designs. In neglecting such a treasure how could we then know what is original. Today the most famous fashion designers are often inspired, in the outwardly from and internal lines of their fashions, by fashion designed during the ages of the past. Designers can find such fashions in books of history and museums. But the historical ages are not equal in the fertility of the originality and novelty of their fashions. Thus the contemporary designer may not find the old designs inspiring so he invents them. The researcher was keen in this paper to include all the basic concept of the art of patchwork 3? and she referred to the historical background of this art as well as its common tools . She also referred to the art of embroidery and beadwork ... etc. To connect the pieces with this classy art (patchwork)/ She discussed some modern producing techniques such as computer. (The study ends with conclusion that suggests designs of the art of patchwork. the paper included io suggested designs.) The study includes inventive ideas. In order words producing great variety from one idea or design with great intellectual and expensive freedom and flexibility in prescribing the creative ideas that are original. The paper is of tow parts. First is the theoretical part which is chapter two of the study that tackles the studies related to the subject mentioned above. The practical part includes a brief explanation of the steps of producing the designs and their supplements. This proves that the art of patchwork is a beautiful art, fit for artistic designs. Hence such designs are not less important and beautiful than other designs that are not based on patchwork. The researcher likes to bring the old to the era of development and technology to make use of it and crystallize our artistic talents. Therefore the study aims to preserve the art of patchwork with the addition of modern and artistic touches with little cost as much as possible.